Long-Term Impact of War, Civil War, and Persecution in Civilian Populations—Conflict and Post-Traumatic Stress in African Communities - Musisi, Seggane; Kinyanda, Eugene (Frontiers in Psychiatry, 2020)
This chapter describes how chronic warfare, as a lived experience, has created significant mental distress in communities on the African continent. Medically, or more specifically psychiatrically, psyho-traumatic stress is defined as a condition characterized by a state of excessive fear, worry and apprehensive expectation occurring on more days than not about a number of potentially stressful events, situations or activities such as happens in severe illness, famine, disasters or war which often causes trauma and ill-health, mentally and physically. This chapter will discuss mental stress consequent to war-fare amongst Africans on the African continent. There is a growing body of research that highlights increasing mental distress in Africa e.g. about sexuality, health, disease, modernity, climate, politics, culture, religion, ethnicities, race, economies etc. Many of these stresses and uncertainties are driven by war. This has shaped many African people’s attitudes and government policies and an increasing scholarly interest in exploring these ‘uncertainties, mental distresses in Africa. The chapter will show how trauma, as seen in conflict/post-conflict settings in Africa, causes significant mental stress and associated social problems as well as medically-defined PTSD syndromes, which cause much morbidity and retard development in many African communities. Taking a classical look at Post-traumatic Stress Disorder, PTSD, the chapter explores the presentation of the various physical and mental clinical syndromes related to war-trauma on the African continent and the consequent health-seeking behaviors of the African peoples in this regard. The term “culture-bound PTSD syndromes” will be introduced and discussed in the broader context of treatment, rehabilitation and prevention on the continent and worldwide. It will also discuss the dilemma of the vicious cycles of trauma driven by appetitive aggression in today’s Africa which portends to further retard socio-economic development and drives the trans-generational perpetuation of ethnic-based conflicts including genocides.